HUBUNGAN KONSENTRASI DENGAN HASIL SHOOTING ATLET PETANQUE PROVINSI JAMBI - Nurzulina Putri, Sinta; Andi Yaksa, Rully; Yuliawan , Ely (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the relationship between concentration and shooting performance among Petanque athletes in Jambi Province. A quantitative correlational research design was employed. The sample consisted of 14 Petanque athletes from Jambi Province selected using a total sampling technique. Concentration was assessed using the Concentration Grid Test (CGT), while shooting performance was measured through a standardized 6-meter Petanque shooting test. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the linearity test, and the Pearson Product-Moment correlation test. The results indicated that the data were normally distributed and satisfied the assumption of linearity. The Pearson correlation analysis revealed a correlation coefficient of r = -0.092 with a significance value of p = 0.755 (p > 0.05), indicating no significant relationship between concentration and shooting performance among Petanque athletes in Jambi Province. These findings suggest that shooting performance is not solely influenced by concentration but may also be affected by other factors, including technical proficiency, physical condition, motor coordination, training experience, and other psychological variables not examined in the present study. Therefore, efforts to enhance shooting performance should adopt a comprehensive approach that addresses multiple determinants of athletic achievement. The findings of this study may serve as a valuable reference for coaches, athletes, and practitioners in sports guidance and counseling in designing more effective athlete development and training programs.